Analisis Pengelolaan Keuangan Desa Dengan Pendekatan Value For Money (Studi Pada Laporan Anggaran Pendapatan Dan Belanja Desa (Apbdes) Desa Jambidan Tahun Anggaran 2014 – 2016) - Wuryanto Putri, Tyas Widoyekti; Susliyanti, Eni Dwi (Jurnal Solusi, 2019)
This study aims to determine the management of village financial which contained in revenue and expenditure budget villages in Jambidan Village for 2014 until 2016 fiscal year with a value for money approach, which is by measuring the economic ratio, efficiency, and effectiveness. With this approach, government of Jambidan Village can know the financial performance that can be used as benchmark in implementing better policy. The method which is used in this analysis is descriptive quantitative research method. The variables that are used including economical, efficient, and effective. While the data were collected by using documentation method which analyzed economic ratio, efficiency ratio, and effectiveness ratio. The results showed that in overall, the Jambidan’s village government is able to manage financial of village in 2014 until 2016 fiscal year period well by using value for money approach.